Development of Augmented Reality Assisted Interactive Multimedia on Human Visual Sense Material to Improve Learning Outcomes of Elementary School Students - Febriyanti, Intania Dinda; Andriani, Aldina Eka (Journal of Educational Sciences, 2025)
This study aimed to describe development design, test the feasibility and effectiveness of AR assisted interactive multimedia on human visual sense material to improve learning outcomes of fifth grade students at SDN Kuningan 04 Semarang City. This research procedure used Research and Development (RnD) method with Borg and Gall development model. Data collection techniques involved test methods (pre-test and post-test) and non-test methods (observation, interviews, questionnaires, and documentation). Data analysis used normality test, t-test, and N-Gain test. This study presents the design AR assisted interactive multimedia developed using Canva and Assemblr Edu consists of menu, usage instructions, material including text, images, animations, videos, AR to strengthen visual media, evaluation (Quizizz), and games (wordwall). The feasibility of AR assisted interactive multimedia is shown by the assessment of material experts by 95% and media experts by 95%, highly feasible category. Supported by response questionnaire from teacher 100% and students 100%, highly feasible category. The average pre-test score was 65.6, the average post-test increased to 85.9. The N-gain test results an average value 0.6 medium category. The conclusion of this study shows that AR assisted interactive multimedia on human visual sense material was successfully developed, feasible and effective for improving learning outcomes.